2003
DOI: 10.1016/s0195-6663(03)00051-5
|View full text |Cite
|
Sign up to set email alerts
|

Use of supermarket receipts to estimate energy and fat content of food purchased by lean and overweight families

Abstract: The aim of this study was to compare the energy and fat content of food purchased for home consumption by households comprising mainly overweight individuals (OH), with those comprising mainly lean individuals (LH). 214 supermarket shoppers and their household were recruited from a Tesco supermarket in Leeds (UK). Households collected supermarket receipts and completed a shopping diary for 28-days, and each member of the household completed a 4-day food record. OH purchased food higher in fat (38% total energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
73
1
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 24 publications
1
73
1
2
Order By: Relevance
“…Table 4 shows that at the individual level, the share of energy from carbohydrates is a little lower for more obese people who consume more of their energy in lipids, although the absolute quantities consumed are higher. Ransley et al (2003) found similarly in the UK that overweight households purchase a larger share of their energy in fat than lean households. Concerning children, they consume more of their energy from carbohydrates and less from proteins.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Table 4 shows that at the individual level, the share of energy from carbohydrates is a little lower for more obese people who consume more of their energy in lipids, although the absolute quantities consumed are higher. Ransley et al (2003) found similarly in the UK that overweight households purchase a larger share of their energy in fat than lean households. Concerning children, they consume more of their energy from carbohydrates and less from proteins.…”
Section: Resultsmentioning
confidence: 87%
“…Ransley et al (2003) use supermarket receipts to estimate the energy and fat content of food purchased by lean and overweight families in the UK, considering the entire household and not its members. On a 28 days basis, they find that overweight households purchase significantly more energy and fat per adult equivalent than lean households.…”
Section: Introductionmentioning
confidence: 99%
“…As gatekeeper of the food supply (41) and an important contributor to neighbourhood nutrition (42) , supermarkets are ideally placed to influence health (43) . To date, consumer food behaviour in the supermarket has mainly been examined through the use of shopping lists (44) and supermarket till receipts (37,45,46) as an index of food consumption or as an estimate of nutrient intake. However, till receipt studies, for example, focus only on actual purchases and are unable to give any insight into the motives for, or justifications of, food choice behaviours.…”
mentioning
confidence: 99%
“…10]. In this manner, Siberian hamsters are not unlike humans that transport food back to their domiciles in their vehicles and store it in their refrigerators/pantries for later consumption, as evidenced by the finding that 85% of all purchased food is eaten at home (50). Therefore, Siberian hamsters are an ideal model for studying the neuroendocrine factors that regulate both appetitive and consummatory ingestive behaviors compared with other rodents, where appetitive behaviors are a smaller part of their naturally occurring ingestive behavior repertoire (41) or where both appetitive and consummatory ingestive behaviors increase or decrease together, such as in laboratory rats and mice (for a review, see Ref 10).…”
mentioning
confidence: 99%